Effect of marble slurry as a partial substitution of ordinary Portland cement in lean concrete mixes. (13th September 2020) - Parmar, Sumit; Das, Sourav Kumar
Abstract: Marble stone is the mostly quarried stone in Rajasthan for its high demand in India and abroad. This quarrying resulted in the generation of waste in a slurry form which was dumped in the nearby landfill sites resulted in a detrimental effect on the soil strata and expanding the landfill area with time. The focus of the study is to explore the outcome of utilization of marble slurry as a partial substitution of ordinary Portland cement by 10%, 20%, 30%, and 40% for lean concrete mixes with an average target compressive strength of 20 MPa or more. To explore the prospect of deployment of marble slurry in cement concrete mechanical properties, durability aspects, and relevant microstructural analysis was performed, and the results have been reported. Though the durability aspect was not purely encouraging, though it was depicted that marble slurry can be utilized as a partial replacement of OPC up to 40% for the purpose for which the investigation has been done. Highlights: Marble slurry utilized as a substitution of OPC by 10%, 20%, 30%, 40%. TGA results indicate that marble slurry did not affect the hydration of OPC. Resistance against carbonation decreases with the increment of marble slurry content. UPV results indicates after 40% substitution concrete was in the good quality zone.